Dynamic crack-interface interactions in SGP laminated glass: An experimental investigation. (July 2018) - Xu, Chengliang; Yuan, Ye; Zhao, Chunlei; Tan, P.J.; Xu, Xiaoqing; Li, Yibing
Highlights: Either crack arrest or branching damage mode may develop in single-edge notch bend test specimen of SGP laminated glass loaded in three point bending. There is a critical distance, between the interface and pre-crack tip, below which the propagating mode-I crack is arrested by the interface. The arrest time prior to branching reduces significantly with increasing impact kinetic energy. A maximum dynamic stress intensity factor criterion is shown to be capable of predicting whether branching damage mode would appear. Abstract: The damage mode (crack arrest or bifurcation ) that develops in SentryGlas ® Plus (SGP) laminated glass under dynamic impact loading is investigated experimentally in this paper. An optical caustic method is employed – which allows simultaneous measurements of the spatial and temporal evolution of crack paths and the dynamic stress intensity factor at the crack tip(s) – to elucidate the effects of interface location and impact kinetic energy upon the fracture morphology, crack propagation velocity and the dynamic stress intensity factor in SENB (single-edge notch bend) test specimens loaded in three-point bending by a drop-weight impact system. Results reveal that there is a critical distance, between the interface and pre-crack tip, below which the propagating mode-I crack is arrested by the interface; otherwise, bifurcated mixed-mode cracks will always appear in the impacted glass layer. A maximum dynamic stress intensity factor criterion is shown to be capable of predicting whether bifurcated mixed-mode cracks would appear in the aforesaid.